MyAbilityAssist - Rudy, Rosevelt Kulong; Patehi, Muhamad Dzulhaziq Hiznie; Md.Ideris@Idris, Izwana; Alihan, Alya Alyani Syazwina; Gatu, Alvin (Universiti Teknologi MARA, Kedah, 2023)
Nowadays, various venues have dedicated facilities for disabled people to ensure equal access. However, finding such facilities while traveling remains a challenge for disabled people because the locations of the facilities are not barrier-free and user-friendly. To address this issue, MyAbilityAssist, a user-friendly application designed for disabled people, has been invented to become a personal helper specifically for them. The application aims to improve the lives of disabled people by assisting them in locating accessible facilities such as parking, toilets, wheelchairs, and many more. MyAbilityAssist is focused mainly in Malaysia to address the limited availability of such facilities in the country and can be used by the locals as well as the tourists that come to visit Malaysia. MyAbilityAssist has a few steps in using it that only require the minimum effort from the users. It utilises location-based services to deliver updated information about the facilities and enables users to plan their journeys while considering accessibility. The Forum Room section allows the users to interact, share stories, seek guidance, and more among the disabled community. It also provides accurate reviews of all of the facilities provided in every location and maintains user safety every time they use the application. With all these features, this app will help disabled people find nearby facilities when they travel in Malaysia. This application will provide equal benefits and value to disabled people and ordinary people. MyAbilityAssist will be commercialised through social media and influencers. We believe that by using these methods, it will be able to grab more attention from society and raise awareness about the positive impact of this application.